Pop Art : a New Generation of Style - Leslie, Richard (London : Tiger Books International, 1997)
Appel, Karel ; Arman ; Artschwager, Richard ; Bacon, Francis ; Blake, Peter ; Brecht, George ; Brown, Roger ; Burri, Alberto ; Cage, John ; Caulfield, Patrick ; César ; Chamberlain, Richard ; Christo ; Conner, Bruce ; Cornell, Joseph ; D'Arcangelo, Allan ; Davis, Stuart ; Dine, Jim ; Dubuffet, Jean ; Duchamp, Marcel ; Evans, Walker ; Fahlström, Öyvind ; Freud, Lucian ; Grooms, Red ; Hains, Raymond ; Hamilton, Richard ; Hartigan, Grace ; Hockney, David ; Hudson, Robert ; Indiana, Robert ; Jess ; Johns, Jasper ; Jones, Allen ; Katz, Alex ; Kienholz, Edward ; Kitaj, R.B. ; Klein, Yves ; de Kooning, Willem ; Lichtenstein, Roy ; Lindner, Richard ; Marisol ; Nilsson, Gladys ; Nutt, James ; Oldenburg, Claes ; Ono, John Lennon & Yoko ; Oppenheim, Meret ; Paik, Nam June ; Paolozzi, Eduardo ; Paschke, Ed ; Phillips, Peter ; Picabia, Francis ; Pistoletto, Michelangelo ; Polke, Sigmar ; Pollock, Jackson ; Rauschenberg, Robert ; Raysse, Martial ; Richter, Gerhard ; Rivers, Larry ; Rosenquist, James ; Ruscha, Ed ; de Saint Phalle, Niki ; Samaras, Lucas ; Schwitters, Kurt ; Segal, George ; Spoerri, Daniel ; Thiebaud, Wayne ; Tilson, Joe ; Tinguely, Jean ; Warhol, Andy ; Wesselmann, Tom ; Westermann, Horace Clifford ; Wirsum, Karl
Engels
boek